HINDUISM AND ISLAMIC ORNAMENTS IN LANGGAR DALEM MOSQUE OF KUDUS - Moh Rosyid (Journal of Islamic Architecture, 2022)
The ancient city, Kudus, Central Java, has unique sites, including ancient ornaments and walls inside Langgar Dalem Mosque. The study aims to reveal that the value of tolerance needs to be cared by every generation of Muslims in Kudus. The data were collected by interview, observation, and literature review. The study used a descriptive qualitative method to analyze the data. The study showed that Langgar Dalem Mosque is a historical-cultural heritage inherited by pre-Islamic Hindus and preserved authenticity by Muslims in Kudus, as a form of the love of cultural works. There are patterns of Javanese, Hindu, and Islamic cultures that decorate the mosque's walls. However, Department of Culture and Tourism of Kudus Regency has not optimally cared for it. So, the initiative of the Mosque management board is the ancient ornaments were painted for their dull color. This could reduce their original aesthetic value and change the cultural heritage values. The ancient wall in Langgar Dalem Mosque with the meaning of cultural tolerance until now has preserved by Sunan Kudus and Moslem generation.